The impact of the retained austenite in the case-hardened steels on the crater wear formation of the PcBN tools - Boing, Denis; Ganea, Anna; Brohede, Ulrika; Stålnacke, Emil; Norgren, Susanne (Wear, 2021)
The finishing operation of transmission components in the automotive industry is widely performed by the hard part turning process, using polycrystalline cubic boron nitride (PcBN) as cutting tool material. Carburizing steels are used in shafts and gears, and after the heat treatment processes, the components have typically 10-30 vol% of retained austenite in the carburized layer. The hard-turning is essentially a process involving high temperatures. The temperature at the tool-chip interface typically reaches the austenitization temperature range of the machined steel. In carburizing steels, the consequence is the generation of crater wear in PCBN tools by the chemical wear mechanism. In this context, this research aims to determine the impact of the retained austenite in the carburized steels on the crater wear formation in the PcBN tools. The 18CrNiMo7-6 steel was used to manufacture the workpieces. During the heat treatment, two carbon potentials (0,64% and 0,72%) and two tempering temperatures (160 °C and 180 °C) were applied to reach two levels of hardness (710 HV and 740 HV) and amount of retained austenite (20% and 27%). To study the wear, hard-turning tests were performed, applying industrial cutting parameters. The PCBN inserts were analyzed by a focus variation microscope (FVM) and a scanning electron microscope (SEM). For the same level of hardness, an increased phase fraction of the retained austenite in the steel increases the crater wear of the PcBN tools. Two complementary hypotheses were framed to explain the results: i. the high fraction volume of retained austenite increases the overall oxidation potential of the iron on the steel, accelerating the chemical degradation of the cBN grains; ii. the high amount of retained austenite reduces the formation of the protective layer on the chip tool interface. The in-depth investigation of chemical degradation is a largely unexplored subject on the wear evaluation of the ultrahard cutting tool. •The research is connected to the automotive industry and the production of transmission components.•The discussion of the hard-turning process in case-hardened steels.•The impact of the retained austenite in the case-hardened steels on the PCBN tool wear.•Discussion about chemical degradation in ultrahard cutting tools (PcBN).